A Single Center Experience in 266 Patients of Infantile Malignancies. (1st September 2014) - Das, Umesh; Appaji, L.; Kumari, B. S. Aruna; KC, Lakshmaiah; Padma, M.; S, Kavitha; Sathyanarayanan, Vishwanath
<x xml:space="preserve">Abstract</x> Introduction: The diagnosis and management of cancer in infantile age group is a significant challenge to pediatric oncologists. Malignancies occurring in infants often have different clinical and biological behavior in comparison to older children. This study was performed with an aim to find out the profile of infantile cancers at a tertiary care cancer center in South India. Methods: The present study was a retrospective analysis of infants presenting with malignancy between 2003 and 2012 to our center in South India. Result: A total of 4588 pediatric patients were registered in the Department of Pediatric Oncology at our institute between 2003 and 2012. Among those, 266 (5.79%) of the patients were infants (0–1 years). There were 65.75% males and 34.25% females. Solid tumors were the most common malignancy in this age group (72.56%). Leukemias were observed in 67 (25.19%) infants. ALL was the most common hematological malignancy (17.29%) followed by AML (5.64%). Common solid tumors in descending orders were neuroblastoma, soft tissue sarcoma, renal tumors, germ cell tumors, retinoblastoma and hepatoblastoma. Thirteen (4.89%) neonates were seen in our study. The most common malignancy in neonates was neuroblastoma. Conclusion: The distribution of malignancy in infants is quite different from that which is found in older children. Although neuroblastoma is the most common infantile tumor in western countries, in our study leukemia is the most common infantile malignancy. Embryonal tumors such as neuroblastoma, Wilms tumor, retinoblastoma, and hepatoblastoma were more prevalent in infants. Solid tumors were the most common malignancy in infants which is followed by leukemia.